Effect of Substrat Concentration and Dosage of MOL (local microorganism) Chicken Development on The Growth and Production of Green Palm Plants (Brassica Chinensia Var. Parachinensis) - Alasri Alasri (AGRONISMA, 2022)
Vegetable farmers in Indonesia tend to use artificial fertilizers or inorganic fertilizers to fertilize mustard greens, the continuous use of artificial fertilizers without returning organic matter will cause the soil to become saturated with certain nutrients, so that in a certain period of time it will reduce crop yields. This study aims to explain the effect of the combination of substrate concentration and MOL dose of chicken manure on the growth and yield of mustard greens. This research was carried out from March 2021 to May 2021, located in Randuagung Village, RT 06 RW 05 Gondang Tengah, Singosari District, Malang Regency with an altitude of ± 487 meters above sea level, the average air temperature ranging from 22˚C-32˚C. In this study, a completely randomized factorial design was used. The first factor is the substrate concentration which consists of 4 levels A1 (20%), A2 (30%), A3 (40%), A4 (50%). While the second factor is the dose of MOL which consists of 3 levels, namely: D1 = recommended dose (20 lt/ha), D2 = recommended dose (40 lt/ha), and D3 = 1.5 recommended dose (60 lt/ha). Ha). The result data were tested by using the BNJ test (Honest Significant Difference) at 5% level and Dunnet test at 5%. The results of this study indicate that there is a significant interaction between the administration of substrate concentration and the dose of MOL on the growth and yield of mustard greens. Substrate concentration and MOL dose interacted at the age of 14 and 21 days after planting on the growth parameters of mustard greens, the best combination treatment was A1D2 with the support of stem diameter data (1.06 cm2), it also gave the best total fresh weight yield of plants with an average average (201.79 g), and dry weight consumption (17.07 g).